Penggunaan Jaminan KSK dan Akta Nikah pada Pembiayaan Murabahah Bi al-Wakalah Perspektif Mashlahah al-Mursalah - Moh. Hamdan Hizbayni Hizbayni (Maliyah : Jurnal Hukum Bisnis Islam, 2020)
This is a field research that aims to answer how the practice of using KSK guarantees and marriage contracts in murabahah al-mursalah financing and how to analyze mashlahah al-mursalah on the practice of using these guarantees. In practice at BMT Amana Madina, murabahah financing is equipped with a wakalah contract, in which the BMT represents the customer to make the purchase of the goods themselves and then the contract is carried out with the determination of the cost of purchase and profit margin in accordance with BMT policies accompanied by the use of collateral as a bond of trust between customers and financial institutions in the form of KSK marriage certificates. The aim are embracing customers and increasing economic equity in the middle to the lower economic community with a financing value of IDR 300,000 to IDR 1,500,000. The implementation of murabahah al-wakalah financing at BMT Amana Madina is in accordance with Islamic law because it has fulfilled the requirements contained in the murabahah and wakalah contracts. Regarding the use of KSK guarantees and marriage certificates in the financing, it is included in the muamalah field which does not have arguments that justify or prohibit it, but has many benefits, both for customers and BMT Amanah Madina. The benefits have met the requirements in the use of mashlahah al-mursalah. So that, the use of KSK guarantees and marriage certificates is included in the scope of mashlahah al-mursalah.